2021
DOI: 10.1016/j.echo.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Correlates of In-Hospital Death in Patients with Acute COVID-19 Infection: The World Alliance Societies of Echocardiography (WASE-COVID) Study

Abstract: Background:The novel severe acute respiratory syndrome coronavirus-2 virus, which has led to the global coronavirus disease-2019 (COVID-19) pandemic is known to adversely affect the cardiovascular system through multiple mechanisms. In this international, multicenter study conducted by the World Alliance Societies of Echocardiography, we aim to determine the clinical and echocardiographic phenotype of acute cardiac disease in COVID-19 patients, to explore phenotypic differences in different geographic regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 27 publications
5
58
1
2
Order By: Relevance
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“…The definition of RVD was heterogeneous across studies, both in terms of parameters and cut-offs used to defined RVD. 13 studies used a combination of several parameters 15 , 18 , 19 , 21 , 24 , 28 , 30 , 33 35 , 38 , 40 , 42 , 8 studies defined RVD according to TAPSE cut-off 14 , 16 , 22 , 23 , 31 , 32 , 36 , 39 , while other or unclear definitions of RVD was used in 8 studies 17 , 20 , 25 27 , 29 , 37 , 41 . In one study, a surrogate of Right Ventricular-Arterial uncoupling, which in turn relates the degree of RVD to the increase of pulmonary pressure, was addressed 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of pulmonary parenchymal and vascular pathology would therefore be expected to have a favorable effect on RV function, to the extent that these treatments are effective. Notwithstanding the underlying mechanisms for RV dysfunction, RV systolic dysfunction is associated with worse clinical outcomes 1 3 , 5 , 8 , 15 , 18 , 19 , 22 , 23 . In comparison with previous studies, the incidence of RV dysfunction was lower in our cohort but when present, it was still associated with worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports linked COVID-19 infection to cardiac abnormalities as determined by echocardiography and CMR 1 23 . The presence of worse right ventricular (RV) function was shown to be associated with worse outcomes, albeit likely related to hypoxemia and pulmonary vascular abnormalities as opposed to primary cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiographic abnormalities, such as left ventricular systolic and diastolic dysfunction as well as right ventricular impairment, are observed in up to half of all COVID-19 patients undergoing echocardiography (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%